PENERAPAN REAL TIME GROSS SETTLEMENT DALAM KEGIATAN USAHA NASABAH DI PT.BANK SUMUT SYARIAH CABANG MEDAN - Isra Hayati; Raja David Indra Kijai (Universitas Muhammadiyah Prof Dr Hamka, 2019)
This study aims to determine the application of Real Time Gross Settlement (RTGS) in customer business activities on services provided by Sharia North Sumatra banks. This research approach uses a quantitative research approach that is based on the philosophy of positivity and the approach to the results of the population or sample. Based on the results of research that has been carried out regarding the Application of RTGS in the Services of Business Activities of customers at PT. Bank Sumut Syariah Branch Brigadier Katamso Medan shows the value of tcount 6.821 with degrees of freedom (dk) n - 1 = 30-1 = 29. Thus the decision-making criteria are: because of the magnitude of tcount 6.821> t table 2.045, and the sig value of RTGS (X) 0.00 <0.05, it can be concluded that the null hypothesis (Ho) is rejected and Ha is accepted, which means that partially the application of RTGS (X) has an effect on customer service activities (Y). Keywords: Real Time Gross Settlement, Customer Business Activities